2008
DOI: 10.1371/journal.pbio.0060260
|View full text |Cite
|
Sign up to set email alerts
|

Structural Homeostasis: Compensatory Adjustments of Dendritic Arbor Geometry in Response to Variations of Synaptic Input

Abstract: As the nervous system develops, there is an inherent variability in the connections formed between differentiating neurons. Despite this variability, neural circuits form that are functional and remarkably robust. One way in which neurons deal with variability in their inputs is through compensatory, homeostatic changes in their electrical properties. Here, we show that neurons also make compensatory adjustments to their structure. We analysed the development of dendrites on an identified central neuron (aCC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(161 citation statements)
references
References 63 publications
15
144
2
Order By: Relevance
“…The fact that total dendritic length within individual neurons did not change significantly over time, despite a threefold increase in dendrite remodeling, suggests that mature cortical neurons may possess an intrinsic mechanism that conserves the total amount of space each neuron occupies. Although this type of homeostasis has been postulated in previous studies that measured dendritic features in Drosophila embryos (Tripodi et al, 2008) and postmortem sections of the hippocampus (Samsonovich and Ascoli, 2006), our data are the first to directly visualize this phenomenon within individual neurons in vivo. Exactly what molecular mechanisms could account for this type of plasticity remain unclear.…”
Section: Discussionmentioning
confidence: 60%
“…The fact that total dendritic length within individual neurons did not change significantly over time, despite a threefold increase in dendrite remodeling, suggests that mature cortical neurons may possess an intrinsic mechanism that conserves the total amount of space each neuron occupies. Although this type of homeostasis has been postulated in previous studies that measured dendritic features in Drosophila embryos (Tripodi et al, 2008) and postmortem sections of the hippocampus (Samsonovich and Ascoli, 2006), our data are the first to directly visualize this phenomenon within individual neurons in vivo. Exactly what molecular mechanisms could account for this type of plasticity remain unclear.…”
Section: Discussionmentioning
confidence: 60%
“…However, other authors have suggested that the arrival of a presynaptic input could act as a stop-growth or stabilization signal for the postsynaptic dendritic arbor. This sprouting would allow the brain to compensate for low network activity (33) and might be an attempt by the brain to adapt (recovering or sparing) to function loss (34). If this were the case, then a more complex dendritic organization should be associated with a loss of memory, and a less developed dendritic organization should be associated with a gain of function.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising because three independent studies have demonstrated that Drosophila motoneuron dendritic branching is affected by neural activity (Hartwig et al, 2008;Duch et al, 2008;Tripodi et al, 2008). By contrast, the mean dendritic radius and the mean length of the individual segments show high constancy between animals (CV < 0.08).…”
Section: Across-animal Constancy Of Metric Dendritic Architecture Parmentioning
confidence: 97%
“…Analyses of the dendritic branching patterns of sensory neurons paired with genetic screens and manipulations have already yielded fundamental insight into key regulatory mechanisms of dendrite development (Grueber and Jan, 2004;Corty et al, 2009). However, much less is known about the specific architecture principles and the constancy of the complex dendritic trees of identified central Drosophila neurons, although these exhibit stereotyped morphologies and have proven useful for analyzing mechanisms of dendritic morphogenesis in the central nervous system (CNS) (Williams and Truman, 2005;Landgraf and Thor, 2006;Tripodi et al, 2008;Hartwig et al, 2008).…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation